Déjouer la Ville Créative ? - Léa Sallenave (EchoGéo)
In 2014, Green Party member Éric Piolle won Grenoble local election. He agrees to support a new festival, the Grenoble Street art Fest’. Since 2015, walls have been adorned with unpublished fiction images which enriched the city with a new label, somehow both "trendy" and "popular", attractive and accessible to all. Like any enterprise taking place in the public sphere, this initiative is both praised (as a way to value the territory and to create social cohesion against spatial disjunctions) and criticized (as exclusionary towards some graffiti artists, as being artistically poor). Either way, the festival becomes a pretext to question the place of street images, both inside (“in”) and outside (“off”). These images allow an analysis of the ways territories build themselves.